Análisis molecular de la cohorte Argentina afectada con distrofinopatía : diagnóstico, asesoramiento genético y caracterización del gen DMD - Luce, Leonela Natalia (2018)
Dystrophinopathies are monogenic recessive diseases linked to the X chromosome and caused by mutations in the DMD gene. This work main objective was to perform a genetic/molecular characterization of the DMD gene. Identifying the molecular alteration is key step for the confirmation of the presumptive clinical diagnosis, the establishment of the patient?s prognosis and the determination of the mutation-dependent therapeutic strategy more suitable for each individual. However, providing a complete genetic counseling to the affected families using carrier screening, prenatal and preimplantation studies remains being necessary in order to avoid the birth of new affected children. In this thesis, 200 boys with presumptive clinical diagnosis of Dystrophinopathy and 12 symptomatic women were analyzed, resulting in confirmation of the disease in 71.7% (152/212). Furthermore, prognosis was established, candidates for the available therapies were identified and the detected mutations were characterized. Regarding carrier status, 69/240 (28.8%) women were established as carriers while 132/240 (55%) were discarded. From the 15 prenatal studies performed: 7 were discarded of being affected, 4 females resulted non-carriers and 3 carriers. On the other hand, here was demonstrated that dystrophin expression is altered in non-myogenic tumors, corroborating the new physiopathological implication of the DMD gene in tumor development.